BABOI: THE TRADITIONAL MOTHER OF SAGULUBBEG MENTAWAI - Kemala, Riski Dwi; Wrahatnala, Bondet (International Journal of Social Science, 2025)
This study discusses the figure of Baboi or Ibu Adat in Mentawai society, particularly in Sagulubbeg Village, Southwest Siberut, as a representation of female authority in the Arat Sabulungan belief system. Using qualitative research methods with ethnography, this study explores Baboi's role in maintaining balance between humans, nature, and the spiritual world through ritual practices, self-symbolism, and ecological knowledge. Baboi acts as a mediator between ancestral spirits and humans, as well as playing a role in maintaining cosmological harmony, which is manifested in Ti'ti Geilat and Sipaggeu. The results of the study show that Baboi holds a strategic function in preserving traditional values and environmental sustainability, especially through the Simatabaik principle, which emphasizes the wise use of resources. In a social context, Baboi also negotiates women's power within patriarchal structures, while also becoming agents of cultural transformation in the era of modernization. This study shows that Baboi is not only a spiritual figure, but also a local feminist ecological symbol that maintains ethical relations between humans and nature. These findings enrich the discourse of feminist anthropology and cultural ecology in the archipelago by emphasizing the importance of indigenous women's knowledge in the social and ecological sustainability system in the Mentawai region